Problematika Manajerial dan Kurikulum Pesantren - Fatoni, Mahfud Heru; Anshory, Isa (Lembaga Yasin AlSys, 2024)
The education system that first appeared in Indonesia was the Islamic boarding school. In its development, Islamic boarding schools have always innovated and transformed themselves, both in terms of the content (material) taught and in terms of methods and management. However, the reality on the ground is that there are still many problems faced by Islamic boarding schools. This research aims to explore managerial problems and Islamic boarding school curriculum. In this research, library research or qualitative methods are used which refer to books and previous research. The results of the research show that Islamic boarding school managerial problems include Islamic boarding school policies being under the authority of the Kyai, the condition of students in terms of clothing, health and behavior as well as the